Learning Curve for Lymph Node Dissection Around the Recurrent Laryngeal Nerve in McKeown Minimally Invasive Esophagectomy - Zhu, Zi-Yi; Luo, Rao-Jun; He, Zheng-Fu; Xu, Yong; Xu, Shao-Hua; Zhang, Qiang (Frontiers in Oncology, 2021)
Background: Compared to open esophagectomy (OE), minimally invasive esophagectomy (MIE) is associated with lower morbidity and mortality. However, lymph node (LN) dissection around the recurrent laryngeal nerve (RLN) is still an important factor that affects the length of the learning curve of MIE. This study aims to evaluate the surgical outcomes of the first nearly 5-year period and explore the learning curve for LN dissection around the RLN in McKeown MIE by a new single surgical team. Methods: A total of 285 consecutive patients who underwent McKeown MIE between March 2016 and September 2020 were included at our institution. According to the cumulative sum (CUSUM) analysis of LN dissection around the RLN, the patients were divided into three groups: exploration period, adjustment period, and stable period. We assessed the impact of surgical proficiency on postoperative outcomes and explored the learning curve for LN dissection around the RLN in McKeown MIE. Results: The CUSUM graph showed that a point of upward inflection for LN dissection around the RLN was observed in 151 cases. After 151 cases, LN around the right and left RLN were dissected thoroughly compared to the exploration and adjustment period (P=0.010 and P = 0.012, respectively), and the postoperative incidence of hoarseness significantly decreased from 11.1 to 1.5% (P＜0.001). Conclusions: Our study results revealed that not only are the LN around the RLN sufficiently dissected but also the incidence of hoarseness significantly decreased in the stable phase. Consequently, the learning curve length was approximately 151 cases for LN dissection around the RLN in McKeown MIE.